(untitled) (TEST Ticontre. Theory Text Translation, 2023)
Giorgio Caproni’s poetry has been influenced by many philosophers, among whom one of the most important is Kierkegaard. This paper therefore aims to analyse the philosopher’s influence on Caproni’s poetry, with the purpose of understanding the thematic and stylistic turning point of the collection Congedo del viaggiatore cerimonioso & altre prosopopee. Caproni tends to dialogue freely with his philosophical source, reworking the cornerstones of Kierkegaard’s thought in a paradoxical way: the concept of despair, the dialogue with the dead, the situation of the Single Individual and the irrationality of faith. La poesia di Giorgio Caproni è stata influenzata da molteplici fonti filosofiche, tra cui una delle più importanti è rappresentata dal pensiero di Søren Kierkegaard. Il contributo mira quindi ad analizzare l’influenza di Kierkegaard sulla poesia di Caproni, con l’obiettivo di comprendere la svolta tematica e stilistica avviata a partire dalla raccolta Congedo del viaggiatore cerimonioso & altre prosopopee. Si noterà che Caproni tende a dialogare liberamente in poesia con la propria fonte filosofica, rielaborando in modo paradossale i capisaldi del pensiero di Kierkegaard: i concetti di angoscia e disperazione, il dialogo con i morti, la condizione del Singolo e l’irrazionalità della fede.